IMPROVEMENT OF STUDENT LEARNING OUTCOMES THROUGH THE TEAM GAMES TOURNAMENT (TGT) COOPERATIVE LEARNING MODEL - Nofriansyah, Nofriansyah; Ahman, Eeng; Supriatna, Endang; Rahayu, Sri; Riyadi, Sugeng (Research and Development Journal of Education, 2025)
This study aims to optimize students' learning outcomes in Economics subjects through the implementation of the cooperative learning model, Team Games Tournament (TGT) type. This research employed Classroom Action Research (CAR) conducted in two cycles, consisting of four stages in each cycle, namely planning, action implementation, observation, and reflection. The subjects of this study involved 33 students of class X.4 at SMA Negeri 3 Cilacap. Based on the research findings, it was revealed that there was an improvement in students' learning outcomes in each cycle. This is evidenced by the increase in the average student score, which rose from 62.78% in the pre-cycle, to 68.78% in the first cycle, and reached 85.03% in the second cycle. Therefore, the application of the cooperative learning model of the Team Games Tournament (TGT) type is proven to be effective in the learning process of Economics to help improve students' learning outcomes at SMA Negeri 3 Cilacap.